KETERKAITAN ANTARA ANTI-INTELLECTUALISM DAN ACADEMIC SELF-EFFICACY DENGAN PERSEPSI MAHASISWA MENGENAI ETIKA TEKNOLOGI INFORMASI DAN ETIKA NON TEKNOLOGI INFORMASI - , Hendra Gunawan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study combines the research sourced from psychological and demographic variables by linking to the ethics that are not related with the use of IT and related IT. In addition, this study also extends previous research by including the variable effectiveness of teaching business ethics into the model to determine whether ethical attitudes of students who have taken the teaching of business ethics have different ethical attitudes of students who do not or have not taken the teaching of business ethics in relation to ethics. Gender and education level included into the model as a control variables. Through a questionnaire survey method to spread the 767 respondents but only 709 are eligible for further analysis. This study were done using a correlation test, independent samples t-test, ANOVA and two ways anova. This study successfully provided support and additional evidence on the relationship between anti-intellectualism, academic self-efficacy with the ethical views of IT and ethics that are not associated with IT. This study also provides evidence that the teaching of business ethics influence on IT-related ethical with support for gender and education level, but could not provide evidence to the ethical that is not related to IT.